Identification of a novel pathogenic variant in CKAP2L and literature review in a child with Filippi syndrome and congenital talipes equinovarus. Issue 7 (29th April 2021) - Karakaya, Taner; Bilgic, Ali Evren; Eris, Deniz; Baser, Burak; Mermer, Serdar; Yildiz, Onur
Abstract: Filippi syndrome (MIM #272440), one of the craniodigital syndromes, is a rare genetic entity with autosomal recessive inheritance and characterized by pre‐ and postnatal growth retardation, microcephaly, distinctive facial appearance, developmental delay/intellectual disability, and variable syndactylies of the fingers and toes. In this report, a further female patient of Filippi syndrome who additionally had a unilateral congenital talipes equinovarus (CTEV), a feature not previously recorded, is described. Genetic testing revealed a novel homozygous frameshift pathogenic variant (c.552_555delCAAA, p.Asn184Lysfs*8) in CKAP2L and thus confirmed the diagnosis of Filippi syndrome. We hope that the newly recognized feature (CTEV) will contribute to expand the clinical spectrum of this extremely rare condition. In view of the paucity of reported cases, the full spectrum of clinical findings of Filippi syndrome necessitates obviously further affected individuals/pedigrees delineation in order to elucidate the etiological and phenotypic aspects of this orphan disease appropriately.